A High‐Energy Density Li‐Ion Hybrid Capacitor Fabricated from Bio‐Waste Derived Carbon Nanosheets Cathode and Graphite Anode. Issue 10 (9th August 2022) - Nanaji, Katchala; Pappu, Samhita; Anandan, Srinivasan; Rao, Tata N.
Abstract: The Li‐ion hybrid capacitor (LIHC) system explores the possibility of achieving both high energy and power density in a single energy storage system with an intercalation anode and capacitive cathode. However, to achieve a high power and energy‐based system, the properties of the cathode electrode material are vital. Here, bio‐waste plant stem‐derived activated porous carbon is explored as a cathode for LIHC application. A specific surface area of 1826 m 2 g −1, enhanced degree of crystallinity, and graphitization results for porous carbon from activation by potassium hydroxide. When employed as supercapacitor material, the device exhibits good rate capability, energy, and power attributes with a specific capacitance of 116 F g −1 (1 A g −1 ). Simultaneously when tested for LIHC application the formulated device shows good capacity retention for 2500 cycles with a high energy density of 125 Wh kg −1 at a power density of 69 W kg −1 . The work demonstrates unique, cost‐effective strategy to develop a crystalline high surface area carbon from any such bio‐waste sources to be employed as potential electrodes for energy storage applications. Abstract : Activated carbon with a specific surface area of 1826 m 2 g −1, and graphene sheet‐like morphology is prepared by KOH activation. The carbon nanosheets are demonstrated for a Li‐ion capacitor as a high‐rate cathode material by employing a commercial graphite anode. The Li‐ion capacitor device exhibits a maximum high energy and power densities of 125 Wh kg −1 and 2083 W kg −1 respectively.